(untitled) (مجلة إحالات, 2026)
In the Hammadid era, Algeria witnessed one of the most fertile eras of its cultural giving. It established relations with several countries, and this contributed to achieving a kind of cultural interaction and benefiting from the other, and this was evident through "Ibn Rashik’s" literary and critical works, and has reflected his works. His cultural interaction with the Maghreb and the cultures coming from the East, and this interaction was based on dialogue and positive discussion, and this is what led him to create works that are still going on.